Analisis Regresi Logistik Biner pada Faktor-faktor yang Mempengaruhi Kesediaan Masyarakat Nagari Paninjauan untuk Divaksinasi Covid-19 - Febrianti Febrianti; Helma Helma (UNIVERSITAS NEGERI PADANG, 2023)
The Covid-19 vaccination rate in Nagari Paninjauan, Agam Regency is still relatively low. Some of the factors that cause it include congenital diseases, fear of side effects, effectiveness of vaccines, and halalness of vaccines. The purpose of this study was to identify the factors that influence people's willingness to be vaccinated. The population in this study amounted to 500 respondents. The sample in this study amounted to 83 respondents obtained using the Cluster Random Sampling method. The community's willingness to be vaccinated against covid-19 as a variable (Y) and science (X_1), worries(X_2 ), hoaxes (X_3), application of health protocols (X_4), profession (X_5), coercion for work (X_6), age (X_7), gender (X_8) as the independent variable in the model fit. The results showed that the binary logistic regression model which is π(x)=(exp (-17,171+2,760x_1-2,813x_3+3,778x_7+3,546x_8 ))/(1+exp⁡((-17,171+2,760x_1-2,813x_3+3,778x_7+3,546x_8 )), where science, hoaxes, age, and gender have a significant effect on people's willingness to be vaccinated against covid-19..